Pengawasan terhadap Bank Tanah: Urgensi, Kewenangan, dan Mekanisme - Hasyim Sofyan Lahilote; Irwansyah Irwansyah; Rosdalina Bukido (Undang: Jurnal Hukum, 2021)
The Omnibus Law for Job Creation establishes a special agency called the land bank agency that manages state land, including planning, acquisition, procurement, management, utilization, and distribution of land. This article revisits on how urgent this land bank is and how its supervisory powers and mechanisms are implemented. This article demonstrates that the formation of the land bank is actually related to problems in land acquisition, especially those intended for infrastructure development, which has triggered land liberalization and caused the increase of land price. Therefore, the land bank is urgent to ensure the availability of land for various development purposes in the future, budget efficiency, as well as to avoid conflicts in the land acquisition process and reduce the side effects of land liberalization. In order to encourage the land bank play its role and function as intended in its formation, good and efficient supervision is also needed. So far, it has been stated in the Omnibus Law for Job Creation that internal supervision is carried out by the supervisory board. Taking into account the relationship of the land bank and the supervisory board with other agencies or institutions that carry out the functions of land and bank as well as their supervision, like the one by the National Land Agency and the Financial Service Authority, it is necessary to have clarity on each role and function to avoid overlap. Abstrak UU Cipta Kerja membentuk badan khusus yang mengelola tanah, yaitu badan bank tanah, yang berfungsi melaksanakan perencanaan, perolehan, pengadaan, pengelolaan, pemanfaatan, dan pendistribusian tanah. Dalam artikel ini dibahas apa sebetulnya urgensi bank tanah ini dan bagaimana pula kewenangan dan mekanisme pengawasannya. Artikel ini memperlihatkan pembentukan bank tanah sebetulnya terkait dengan permasalahan dalam pengadaan tanah terutama yang diperuntukkan bagi pembangunan infrastruktur, sehingga memicu terjadinya liberalisasi tanah dan mengakibatkan harga tanah melambung tinggi. Karena itu, bank tanah urgen dalam rangka menjamin ketersediaan tanah untuk berbagai keperluan pembangunan di masa yang akan datang, efisiensi anggaran, serta mengurangi konflik dalam proses pembebasan tanah dan dampak buruk liberalisasi tanah. Dalam rangka mendorong agar bank tanah berperan dan berfungsi sebagaimana dikehendaki dalam pembentukannya, maka diperlukan pengawasan yang baik dan efisien pula. Sejauh ini dalam UU Cipta disebutkan pengawasan dilakukan secara internal oleh dewan pengawas. Dengan mempertimbangkan adanya keterkaitan bank tanah dan dewan pengawas ini dengan badan atau lembaga lainnya yang menjalankan fungsi pertanahan dan bank serta pengawasannya juga, misal Badan Pertanahan Nasional dan Otoritas Jasa Keuangan, maka adanya kejelasan terhadap masing-masing peran dan fungsi sangatlah diperlukan, agar tidak malah terjadi tumpang tindih.